2018
DOI: 10.1080/10437797.2018.1474148
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Relationship Between Resilience and Professional Skills: A Longitudinal Study With Social Work Students

Abstract: This study analyzed the relationship between the resilience developed by social work students and the professional skills acquired during their university degree program. A longitudinal study was conducted over 4 academic years. Participants were 73 social work students at the University of Malaga (Spain). The results show a gradual increase in the development of resilience and in the acquisition of professional skills among the students during the 4-year period. Panel model analysis shows that the two process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…According to another result of the research, the increase of the participants' grade level explains their resilience significantly and positively. Researches conducted on this subject found that the resilience of university students increases as their ages increase (Durmuş and Okanlı, 2018;Kılıç and Alver, 2017;Palma-García, Jacinto and Hombrados-Mendieta, 2018). Therefore, it can be said that the results mentioned are consistent with the results obtained from this research.…”
Section: Discussionsupporting
confidence: 86%
“…According to another result of the research, the increase of the participants' grade level explains their resilience significantly and positively. Researches conducted on this subject found that the resilience of university students increases as their ages increase (Durmuş and Okanlı, 2018;Kılıç and Alver, 2017;Palma-García, Jacinto and Hombrados-Mendieta, 2018). Therefore, it can be said that the results mentioned are consistent with the results obtained from this research.…”
Section: Discussionsupporting
confidence: 86%
“…It is important to realize that both household and occupational responsibility may have a two‐way relationship with resilience, whereby lack of resilience may prevent individuals from seeking or persevering with responsibility and lack of responsibility may reciprocally weaken resilience. A similar reciprocal relationship has been observed between resilience and professional competence 28 ,. 29 Competence in one's professional career is a significant predictor of resilience, which allows individuals to overcome adversity and achieve success in the workplace, 29 while preserving mental well‐being 30 .…”
Section: Discussionsupporting
confidence: 70%
“…CPPs in isolated communities may have access to fewer resources and increased caseloads. Second, our study cannot draw conclusions about how engaging in resilient behaviors impacts the professionals and the children they support ( Palma-García, Gómez Jacinto, & Hombrados-Mendieta, 2018 ), both during the pendency of this pandemic and after it concludes. Third, we do not consider here many aspects of the work environment that may play a role in professionals’ success, including provision of necessary protective gear during a pandemic, job flexibility, and open and honest communications about mental health.…”
Section: Discussionmentioning
confidence: 99%